Study on stress distribution and prefabricated crack propagation law of shale under high voltage electric pulse load in water - Xiankai BAO; Bin JIANG; Ning WU; Guangqin CUI; Chaoyun YU; Tong ZHANG; Xiaofan ZHANG (Meikuang Anquan)
To study the stress distribution, crack propagation length, and deflection angle of shale under the action of high-pressure electric pulse loads in water, the stress superposition principle was employed to theoretically investigate the distribution of primary and induced stress fields in shale under the influence of high-voltage electric pulses in water. Coupled with a high-voltage electric pulse fracturing system in water, underwater high-voltage pulse rock-breaking and prefabricated crack propagation experiments under triaxial pressure were conducted. The effects of various prefabricated crack lengths (10, 20 mm) and angles (60°, 90°, 120°) on crack propagation were examined from a macroscopic perspective. Numerical simulations of underwater high-voltage pulse rock-breaking and prefabricated crack propagation were performed using the extended finite element method (XFEM) in ABAQUS software. The influence of different prefabricated crack lengths and angles on crack propagation was further analyzed from a microscopic perspective. The research results indicate that: under the action of high-voltage electric pulse loads in water, the surrounding wellbore walls are prone to tensile failure, and cracks are prone to competition, deflection, and other phenomena under the combined action of the original in-situ stress field and induced stress field. The larger the angle and length between prefabricated cracks, the greater the total deflection angle, the longer the extension length, and the weaker the interference between cracks. The stress concentration phenomenon at the tip and deflection of prefabricated cracks is obvious, and the stress field between the prefabricated cracks is concentrated in the region defined by the angles. As the angle between the prefabricated cracks increases, the extent of the concentrated stress region gradually decreases, accompanied by a corresponding reduction in stress values. Consequently, the crack propagation deflection angle decreases, and the mutual interference between cracks diminishes progressively.